2021
DOI: 10.51470/plantarchives.2021.v21.s1.122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Causal Agent of Sooty Stem and Branches Wilt Disease in Some Trees in Iraq

Abstract: The study was conducted at the College of Agricultural Engineering Sciences-Department of Plant Protection in 2018-2019 Baghdad/Iraq. The research aims to molecular identification of the fungal pathogen Neoscytalidium sp. the causal agent of the wilt branches disease on pomegranate, mulberry, apple, castor, and rubber by 18S ribosomal RNA gene and DNA sequencing, to demonstrate the pathogenicity, and host range of the fungal isolates. Five fungal isolates have been recoverd from the infected branches belonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The fungi were Isolated from the, hospice branches of the following sooty rot-infected trees; apple (Malus domestica), mulberry (Morus alba) and castor (Populus euphratica). The infected branches were cut off into smaller parts (0.5 cm near the infected area) and sterilized with 20% of sodium hypochlorite solution for 3 minutes [7]. Then, the pieces were washed with sterile distilled water 3 times and dried with filter paper.…”
Section: Isolation and Identification Of The Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungi were Isolated from the, hospice branches of the following sooty rot-infected trees; apple (Malus domestica), mulberry (Morus alba) and castor (Populus euphratica). The infected branches were cut off into smaller parts (0.5 cm near the infected area) and sterilized with 20% of sodium hypochlorite solution for 3 minutes [7]. Then, the pieces were washed with sterile distilled water 3 times and dried with filter paper.…”
Section: Isolation and Identification Of The Pathogenmentioning
confidence: 99%
“…The previous studies indicated that the most susceptible trees to the infection are; Orange trees, English nuts, Mango, Ficus, Apple, castor, rubber pomegranate, mulberry, tiger skin plants and papaya [6,7,8,9,10]. In order to control fungal infection, [11] referred to the possibility of using kaolin as it interferes with the ability of the fungal penetration of the leaf surface.…”
Section: Introductionmentioning
confidence: 99%
“…These results are not consistent with what was mentioned by [25] as the length of the spores ranged between 4-16.5 μ and a width between 8.5 μ . While [14] recorded the length of the spore between 4-12 μ and the width between 2.5-8 μ . The length of the spore ranged from 6-12 μm and its width was 3-6 μm [41].…”
Section: Spore Dimension Measurement Of Neoscytalidium Sppmentioning
confidence: 99%
“…The name of the fungus was changed to Fusicoccum dimidiatum by Farr in 2005 based on genetic analysis . [13] reassessed the family Botryosphaeriaceae and clarified that the genus Fusicoccum is multiancestral and suggested the name of the genus Neoscytalidium to include all the fungi identified by Nattrass, and thus the correct name for the fungi species described and identified by Nattrass is Neoscytalidium based on molecular analysis [14] The ITS region (Internal Transcript Spacer) is used in genetic taxonomic studies, where it represents a sequence of nitrogenous bases present in the ribosomal DNA (rDNA) of the gene. As a result of the variation in the sequences of the ITS regions in DNA, it is an important characteristic, as each genus and fungal species has its own sequence that differs from the species and other races [15] The naming of the fungus is very confusing, as most research indicates that the naming of the fungus Hendersonula is constantly changing.…”
Section: Introductionmentioning
confidence: 99%